2020
DOI: 10.3390/pharmaceutics12050393
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Functional Excipients in Solid Oral Dosage Forms to Overcome Poor Drug Dissolution and Bioavailability

Abstract: Many active pharmaceutical ingredients (APIs) exhibit poor solubility and low dissolution rates in aqueous environments such as the luminal fluids of the gastrointestinal tract. The oral bioavailability of these compounds is usually very low as a result of their poor solubility properties. In order to improve the bioavailability of these poorly soluble drugs, formulation strategies have been applied as a means to improve their aqueous solubility and dissolution rates. With respect to formulation approaches, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…According to USP 37, ASE was considered practically insoluble in water (50.0 ± 1.5 mg/L) at room temperature, and the water dissolution test showed that no more than 45% of ASE dissolved in 45 min. These characteristics influence the in vivo active behavior, reducing its in vivo absorption and bioavailability [ 28 ]. For this reason, we considered CD as a material to improve ASE solubility and to enhance the dissolution rate [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to USP 37, ASE was considered practically insoluble in water (50.0 ± 1.5 mg/L) at room temperature, and the water dissolution test showed that no more than 45% of ASE dissolved in 45 min. These characteristics influence the in vivo active behavior, reducing its in vivo absorption and bioavailability [ 28 ]. For this reason, we considered CD as a material to improve ASE solubility and to enhance the dissolution rate [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that certain drugs form a complex with Captisol ® by hydrophobic interactions [ 15 , 16 , 17 ]. The inclusion complexation between cyclodextrin and a drug can generally increase the aqueous solubility of the aforementioned drug, and increase the dissolution rate [ 54 ]. It was previously reported that the solubility of remdesivir can be increased by Captisol ® , and Veklury ® , and the commercial product containing remdesivir includes Captisol ® to solubilize remdesivir for the IV solution formulation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that certain drugs form a complex with Captisol® by hydrophobic interactions [15][16][17]. The inclusion complexation between cyclodextrin and drug can increase the aqueous solubility of drug, and increase the dissolution rate [49]. It was previously reported that the solubility of remdesivir can be increased by Captisol®, and Veklury®, the commercial product containing remdesivir, includes Captisol® to solubilize remdesivir for the IV solution formulation [15].…”
Section: Remdesivir In Tff Powder Compositions Can Be Dissolved Absomentioning
confidence: 99%